The geochemical effects of olivine slurry replenishment and dolostone assimilation in the plumbing system of the Franklin Large Igneous Province, Victoria Island, Arctic Canada - Hayes, Ben; Lissenberg, Cornelis Johan; Bédard, Jean; Beard, Charlie (Contributions to Mineralogy and Petrology, 2015)
The Neoproterozoic (~723–716 Ma) Franklin Large Igneous Province exposed on Victoria Island in the Canadian Arctic is comprised of a sill-dominated magma plumbing system overlain by the coeval Natkusiak flood basalts. We have investigated three sections, separated by a total of >50 km of distance, of a sill (the Fort Collinson Sill Complex) emplaced just above a prominent sedimentary marker unit. The sill is characterized by a basal olivine-enriched layer (OZ: up to 55 % olivine) and an upper gabbroic unit. The observed diversity of olivine compositions in the OZ implies that bulk-rock MgO versus FeO arrays reflect accumulation of a heterogeneous olivine crystal cargo. We suggest that the OZ was formed as a late olivine slurry replenishment in a partially crystallized gabbroic sill, propagating for over 50 km along strike. This interpretation is consistent with Pb-isotope data, which show that at least three geochemically distinct magmas were emplaced into the Fort Collinson Sill Complex. The OZs exhibit a gradual westward evolution toward more Fe-rich bulk compositions. This is best explained by progressive mixing of the replenishing olivine slurry with a resident gabbroic mush during westward flow. Pb-isotopic signatures suggest that magmas near the inferred conduit feeder assimilated small amounts (<10 %) of dolostone country rock, which may have locally buffered olivine compositions to high-Fo contents.